THE EFFECT OF RETURN ON ASSETS, CURRENT RATIO, AND DEBT TO EQUITY RATIO ON STOCK PRICES IN PROPERTY AND REAL ESTATE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2020–2024 - Nabila Azmi; Wiliam; Florentia Jasmine; Asda Ria Sitorus; Nasib (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The purpose of this study is to analyze the effect of Return on Assets, Current Ratio, and Debt to Equity Ratio on stock prices in Property and Real Estate sector companies listed on the Indonesia Stock Exchange. This study uses secondary data in the form of companies’ financial statements for the 2022–2024 observation period. The sample consists of 10 companies selected from a total of 91 companies. The data analysis technique used in this study is Multiple Linear Regression Analysis with the assistance of SPSS version 25. The results show that Return on Assets has a positive and significant effect on stock prices, the Current Ratio has a positive and significant effect on stock prices, and the Debt to Equity Ratio has a negative and significant effect on stock prices.